2012
DOI: 10.1111/bpa.12012
|View full text |Cite
|
Sign up to set email alerts
|

18‐Year‐Old Woman with a Dural Mass

Abstract: We report a case of a dural-based chondroma in the right frontal extra-axial region. Chondromas are benign cartilaginous tumors which are uncommon intracranially. Their diagnosis should be predicated on the exclusion of a chondrosarcoma and clinical studies should be performed to rule out any underlying tumor predisposition syndromes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 11 publications
(18 reference statements)
0
7
0
1
Order By: Relevance
“…Some authors suggested that the tumor may originate from meningeal fibroblasts metaplasia, others suggested that the tumor may arise from multipotential or perivascular mesenchymal cells or aberrant nests of cartilage forming cells in the dura mater. Traumatic displacement of cartilage is another theory proposed in accordance to existing cases of head trauma presenting with chondroma at the trauma site .…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Some authors suggested that the tumor may originate from meningeal fibroblasts metaplasia, others suggested that the tumor may arise from multipotential or perivascular mesenchymal cells or aberrant nests of cartilage forming cells in the dura mater. Traumatic displacement of cartilage is another theory proposed in accordance to existing cases of head trauma presenting with chondroma at the trauma site .…”
Section: Discussionmentioning
confidence: 81%
“…The age of patients reported in the literature ranges from 15 months to 60 years. There is no sex predominance .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Osteocartilaginous tumors are exceedingly rare, are usually dural‐based, develop in the skull and only secondarily displace dura and brain . To our knowledge, extraosseous osteoma, chondroma, osteochondroma, mesenchymal chondrosarcoma, osteosarcoma and aneurysmal bone cyst have been seldom described in the CNS. A few cases of unusual dura‐based periosteal osteoblastoma have also been reported in cranial bones, such as temporal bone and frontal cranial bone .…”
Section: Discussionmentioning
confidence: 99%
“…Primary intracranial chondrosarcomas are rare, representing <0.15% of all intracranial tumors. Most of them arise from underlying precursor cartilaginous or bony lesions of the axial skeleton, and the most common type of intracranial chondrosarcoma is the mesenchymal type [3,4]. Primary intracranial chondrosarcomas may present with radiation sarcoma [5].…”
Section: Introductionmentioning
confidence: 99%